MACROCHELID MITE (ACARI: GAMASIDA) ASSOCIATED WITH DUNG BEETLES IN BALURAN NATIONAL PARK, EAST JAVA, INDONESIA - Dwibadra, Dhian; Hartini, Sri (Puslitbang Aptika dan Ikp, 2010)
Eight mite species of the family Macrochelidae (Acari: Gamasida) were collected from the body surface of dung beetles in Baluran National Park, East Java, Indonesia. Of these, one species, Macrocheles subwallacei sp. nov., was described as new to science. Female of Macrocheles crispa (Berlese, 1910) was redescribed and the male was described for the first time. The remaining six species were Neopodocinum jaspersi (Oudemans, 1900), M. dispar (Berlese, 1910), M. hallidayi Walter & Krantz, 1986, M. entetiensis Hartini & Takaku, 2005, M. jabarensis Hartini & Takaku, 2003 and M. persimilis Hartini, Dwibadra & Takaku, 2007.